Managerial Accounting - Garrison Ray.H (McGraw-Hill, 2003)
Garrison/Noreen has been- and still is- the market-leading text in managerial accounting, having educated close to 2 million students since its inception. In short, Garrison is the Guide in Managerial Accounting. The lighthouse on the cover symbolizes that for this difficult course, Garrison's comprehensive but manageable coverage, author-written supplements, and peerless end-of-chapter material makes it a safe and dependable choice for instructors and students alike. The loyalty and following it has achieved is due to the authors unwavering commitment to three simple principles: relevance, balance, and clarity.